Exploring EFL Teachers' Strategies to Overcome Students' Boredom in Reading English Texts: A Case Study at Junior High School Level - Pupuh, Ayu; Ekowijayanto, Mochlis (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates various strategies used by English as a Foreign Language (EFL) teachers to counteract students' boredom while reading English texts. The study adopts a qualitative approach, utilising semi-structured interviews with EFL teachers from diverse educational settings. This research was conducted at a junior high school in Paiton, Probolinggo, and focused on teacher strategies to overcome reading boredom in English lessons. Data was gathered through interviews with EFL teachers, emphasising their innovative methods and the efficacy of these strategies in reducing student disengagement. The findings show that various strategies, such as reading with a picture, scanning for interpreted vocabulary, and reading with technology, are used to make reading more interesting and enjoyable. The study gives insights into the problems instructors face and outlines recommended practices for developing a more dynamic and engaging reading experience. These insights have implications for EFL teaching practice and can improve reading outcomes in English learning.